Pemaksimalan Penyidikan Tindak Pidana Keimigrasian oleh PPNS (Studi Kasus Pt. Atrinco Mulia Sejati) - Ahmad Ady Majeng; M. Iman Santoso; Chairul Huda (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2023)
This study aims to find out the application of criminal investigations against corporations and the impact resulting from the implementation of immigration criminal investigations against corporations. The method used is normative-empirical and further deepened through the collection and processing of qualitative data. The results of this study indicate that PT. Atrinco Mulia Sejati was proven to have committed an immigration crime, namely he was unable to carry out his obligations as a guarantor and in decision No. 397/Pid.Sus/2017/PN.Jkt.Ut sentenced Risnawati as a representative of PT. Atrinco Mulia Sejati and no other crimes were imposed apart from the corporation. In addition, there is an impact arising from the decision. Every court decision issued regarding an immigration crime can have a deterrent effect on perpetrators of criminal acts and prevent or suppress the possibility of the same crime being committed again, either by the same or a different subject. However, if you look at the facts on the ground, there are still forms of immigration violations committed by foreigners and the guarantor who guarantees the foreigner while in Indonesia does not know who the guaranteed foreigner is.